Leveraging Sustainability: How Firm Size Shapes the Value-Creating Effects of Carbon Emission Disclosure and Environmental Performance on Firm Value - Ranti Ardelia; Veronika Santi Paramita (Indonesian Scientific Publication, 2026)
As the severity of global warming escalates, investors increasingly favor firms demonstrating strong environmental responsibility, underscoring the growing importance of sustainability in capital market decisions. This study examines the effect of carbon emission disclosure and environmental performance on firm value, considering firm size as an interaction factor within IDX-listed energy firms during the 2019–2024 period. This study utilizes longitudinal secondary datasets sourced from audited financial disclosures and corporate sustainability reports. The sample consists of 11 energy companies selected through purposive sampling. Carbon emission disclosure is measured using the GRI 305 index. Environmental performance is proxied by PROPER ratings. Firm value is calculated by price-to-book value (PBV), and the natural logarithm of total assets represents firm size. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA). The results indicate that carbon emission disclosure does not significantly affect firm value. Environmental performance, however, shows a negative influence on corporate valuation. Furthermore, firm size does not moderate the relationship between carbon emission disclosure and firm value, but it significantly moderates the relationship between environmental performance and firm value. These findings indicate that environmental performance is generally perceived by the market as a cost-intensive activity, exerting a negative effect on firm value, particularly for smaller firms. However, the positive interaction between environmental performance and firm size suggests that larger firms can leverage their scale to translate environmental efforts into relatively greater value creation, highlighting the importance of aligning sustainability strategies with firm size for long-term value.